HOMESTAYS: CATALYSTS FOR ECO-TOURISM PROMOTION IN HIMACHAL PRADESH (CAHIERS MAGELLANES-NS, 2024)
The state that stands out the most on the Indian tourism map is Himachal Pradesh. Shimla became the summer capital of the British after they saw how beautiful Himachal Pradesh was. The phrase "a destination for every season and all reasons" is now used to describe Himachal Pradesh. Over the past ten years, the average number of visitors to Himachal Pradesh has exceeded one crore. A growing number of people seeking solace from the chaos of urban jungles are discovering the dev Bhoomi (Thakur, 2017). This research explores the role of homestays in promoting eco-tourism in the prominent tourist destinations of Manali, Dharamshala, and Shimla in Himachal Pradesh. The study aims to understand how homestays contribute to sustainable tourism, economic development, and cultural preservation in these areas. Secondary data from various sources, including government reports, tourism studies, and academic literature, have been used to analyze the current state and impact of homestays. The findings indicate that homestays significantly support eco-tourism by providing environmentally friendly accommodations and promoting local culture and traditions. Economic benefits to local communities are substantial, but challenges such as lack of infrastructure and regulatory support persist. This study highlights the need for strategic policies and better infrastructure to enhance the sustainability and growth of the homestay sector. The insights gained can help policymakers, tourism developers, and homestay operators foster a more inclusive and sustainable tourism industry in Himachal Pradesh.